"Not as my Neighbor´": How Misinformed Narratives Surrounding the FARC are Hindering the Social Reintegration of its Demobilizing Combatants - Gibson, Sam (In Factis Pax: Journal of Peace Education and Social Justice, 2018)
With the current group-demobilization of the Fuerzas Armadas Revolucionarias de Colombia-FARC, this study offers a timely exploration on the relationship between how the guerrilla group and its members are viewed and their capacity to return to society as civilians. Through a Grounded Theory qualitative approach based on interviews and focus-groups with former FARC members, as well as ex-paramilitary and wider civil society, findings show thathow the group members are received back into communities hinges on dominant, national-narratives surrounding the FARC which blur the group and its former-members as terrorists and criminals. Therefore, despite a widespread desire for a negotiated end to the conflict, most Colombians are not prepared to accept what this actually entails, i.e. the reintegration of a collectively-demobilizing FARC back into society —showing reluctance towards the social integration of its excombatants, whether as co-workers or neighbors, and even less so as citizens or friends. However, the counter-narratives of the excombatants, and empirical evidence show great inconsistencies and falsehoods in these narratives. Moreover, the returnees’ reactions to this hostile climate is often to be secretive about their past and keep a low profile with minimal social interaction whilst striving towards what they conceive as being a “normal” citizen—that is studying and/or working (termed here as the “secret-citizen” narrative). The study demonstrates that the current model—akin to reinsertion—will not lead to a fuller reintegration unless national-narratives shift significantly, and the FARC and its excombatants are at a very minimum accepted as citizens in a post-conflict society.